Pengembangan Prototipe Sistem Network Rendering Alternatif Berbasis JPPF - I Made Putrama; I Wayan Adi Sparta; I Gede Mahendra Darmawiguna; Gede Saindra Santyadiputra (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Rendering is a stage to turn a model into a 3D animated video form. Rendering process takes a long time and requires hardware support with high specifications. Unfortunately, computers for rendering purpose with high specifications are generally very expensive. An alternative solution to this problem is to utilize grid computing technology that can take advantage of some ordinary computers configured in the network. Together, those computers can help complete rendering process more quickly. In this paper, the rendering solution is achieved by combining the grid computing technology-based framework, called JPPF, that can be integrated using Blender 3D. Blender 3D is one of the common software used in making animated films. In this paper, the solution result is also compared with the one from the network-based rendering feature of the Blender 3D, called Network Rendering, as a performance benchmark. The comparison results show that this alternative solution works with relatively better performance and flexibility and is easier to operate than the features provided in 3D Blender.